Non-price determinants on intention to purchase of organic foods in State of Kedah, Malaysia - Tan, Yew Kuan (2015)
Organic food is becoming popular among todays‘ millennial consumers as consumer awareness towards healthy lifestyle had increased. Scholars and practitioners had put much consideration in understanding what drive consumers‘ attitude and behavior towards organic food mainly to strengthen their strategies and tactics to dominate the market. As past literatures consistently highlighted that organic food enjoyed slightly higher price, this study attempts to examine the influence of non-price determinants on intention to purchase organic food. The study among 117 respondents in state of Kedah, Malaysia revealed that environmental concern has a significant relationship with intention to purchase organic food. Another two determinants namely, product knowledge and attitude towards organic food found insignificant in influencing intention to purchase organic food. As a result, practitioners are urged to aggressively promote the benefits of organic food among public mainly to enhance their attitude towards organic food. Future study should focus in a larger sample as well as consider other non-price determinants on intention of purchase organic food